2014
DOI: 10.1117/12.2059637
|View full text |Cite
|
Sign up to set email alerts
|

Fibre optic humidity sensor designed for highly alkaline environments

Abstract: This paper presents the design of a sensor packaging for a Fibre Bragg Grating (FBG) based fibre optic humidity sensor. The evaluation of the developed fibre optic sensor was performed under experimental conditions and verified its capability to withstand highly alkaline environments. Therefore, the sensor can be applied to monitor the concrete humidity level and thus to indicate the maintenance of concrete structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Therefore, the study reported here underpins a body of research carried out by CUL in the development and application of photonic sensors (Alwis et al, 2017); Alwis et al, 2013a); Alwis et al, 2013a;Alwis et al, 2013b;Bremer et al, 2014a, Bremer et al, 2014bSun et al, 2012)…”
Section: Sensors Fabricationmentioning
confidence: 85%
“…Therefore, the study reported here underpins a body of research carried out by CUL in the development and application of photonic sensors (Alwis et al, 2017); Alwis et al, 2013a); Alwis et al, 2013a;Alwis et al, 2013b;Bremer et al, 2014a, Bremer et al, 2014bSun et al, 2012)…”
Section: Sensors Fabricationmentioning
confidence: 85%
“…A detailed description of the operation and packaging of the FBG based humidity sensor can be found elsewhere [16]. The FBG based humidity sensor employed consists of a bare and a polyimide (PI)-coated FBG, with both FBGs multiplexed in series along the fibre.…”
Section: Fbg Based Humidity Sensormentioning
confidence: 99%
“…Although not measured directly, based on prior work and a knowledge of how the characteristics of these devices change with coating thickness, the humidity sensitivity and response time, the thickness of the PI coating was estimated to be approximately 35 m [18]. As the packaging of the FBG based humidity sensor has no direct influence on the sensor response [16], the response time and sensitivity can be optimized by changing the coating thickness [18]. However, in terms of detecting leakages in sewerage tunnels the response time and sensitivity of the current device were designed to be well suited to this specific application.…”
Section: Evaluation Of Fbg Based Humidity Sensormentioning
confidence: 99%
See 1 more Smart Citation
“…So far, many different non-invasive techniques have been tested [4], but they all have some limitations: some are not applicable in presence of magnetic fields (NMR), others are not capable of detecting small water content variations (gamma and x-rays), their investigation depth is limited (gamma and x-rays, radar based methods), or they need access to both sides of the investigated object (microwave methods) [5]. In recent years, many studies have demonstrated that optoelectronic technologies can be successfully used in several branches of civil engineering [6], including the determination of moisture content in porous media [7][8][9]. One emerging technology exploiting optical fibres is Distributed Temperature Sensing (DTS), a flexible and powerful technique that provides the measurement of the temperature profile along a standard optical fibre with high accuracy and spatial resolution.…”
Section: Introductionmentioning
confidence: 99%